A study of degraded skeletal samples using ForenSeq DNA Signature™ Kit. (December 2017) - Almohammed, E.; Zgonjanin, D.; Iyengar, A.; Ballard, D.; Devesse, L.; Sibte, H.
Abstract: Recent advances in massively parallel sequencing (MPS) has become a very promising technology for massive genetic sequencing[1] . In this study Illumina ForenSeq™ DNA Signature Prep Kit was tested to determine if MPS offers a more comprehensive evaluation of degraded samples than the traditional fragment analysis/capillary electrophoresis based method. The Illumina ® ForenSeq™ DNA Signature MPS Kit, includes 200 genetic loci[2] . The use of NGS would therefore reduce the analysis time and augment the identification of human remains. In this context we aimed to analyse the hard tissue degraded samples using Illumina ® ForenSeq™ DNA Signature MPS Kit. These samples had given partial profiles with dropout at several loci with GlobalFiler™ kit previously. The MPS kit showed that it is highly sensitive, aids in higher allele recovery for STR loci and provides valuable information about biogeographic ancestry, identity and phenotypic features from a single analysis. The work resulted in highly successful amplification and sequencing of 30 degraded bone/teeth samples using MPS method.